Bela H. Banathy Learning Design Model Based on Interactive Multimedia at Madrasah Ibtida'iyah Ma'arif Ketegan - Ulya , Himmatul; Zainiyati , Husniyatus Salamah; Izzi , Muhamad Nur Lutfi Ainul (Al-Insyiroh: Jurnal Studi Keislaman, 2022)
The purpose of this research is to know the concept of learning design of Bella H. Banathy model, in addition to seeing the advantages and disadvantages of learning design of Bella H. Banathy model. This study uses a qualitative method. Data collection techniques using interview techniques, observation and documentation. The results showed that the Bella H. banathy model was oriented towards learning outcomes. The approach used is an approach based on the fact that learning activities are complex, consisting of several components that are well integrated with each other to achieve the best results, which can be called a systems approach. In addition, there are several advantages and disadvantages to the Bella H. Banathy model. Its advantages include being able to formulate and analyze specific goals, develop criteria based on formulated tests, analyze students' initial abilities, and evaluate improvements. While the weakness is a little so it is feared inefficient.